Estimation of Atenolol by Reverse Phase High Performance Liquid Chromatography - Naveen Kumar (E-Journal of Chemistry, 2010)
A simple, precise, sensitive, fast and accurate high performance liquid chromatography method has been developed for the determination of atenolol using mixture of phosphate buffer and acetonitrile (53:47 v/v) as mobile phase. Buffer was prepared by mixing 0.02 M K2PO4 and 0.003 M KH2PO4 in equal proportion. Detection was carried out using UV detector at λmax 230 nm. Column was ODS and dimensions of column was 25 mm × 4.6 mm. Atenolol was eluted out at retention time of 2.1 min. Method was validated at 1.2 mL/min flow rate. Calibration curve was linear between ranges of 40 to 200 mcg concentration. The limit of detection was calculates 120 nano gram and limit of quantitation is 510 nano gram. The relative standard deviation (RSD) of atenolol was 0.6. The percentage recovery of atenolol was 99.6%.